Subliminal Face Emotion Processing: A Comparison of Fearful and Disgusted Faces - Khalid, Shah; Ansorge, Ulrich (Frontiers in Psychology, 2017)
Prior research has provided evidence for (1) subcortical processing of subliminal facial expressions of emotion and (2) for the emotion-specificity of these processes. Here, we investigated if this is also true for the processing of the subliminal facial display of disgust. In Experiment 1, we used differently filtered masked prime faces portraying emotionally neutral or disgusted expressions presented prior to clearly visible target faces to test if the masked primes exerted an influence on target processing nonetheless. Whereas we found evidence for subliminal face congruence or priming effects, in particular, reverse priming by low spatial frequencies disgusted face primes, we did not find any support for a subcortical origin of the effect. In Experiment 2, we compared the influence of subliminal disgusted faces with that of subliminal fearful faces and demonstrated a behavioral performance difference between the two, pointing to an emotion-specific processing of the disgusted facial expressions. In both experiments, we also tested for the dependence of the subliminal emotional face processing on spatial attention – with mixed results, suggesting an attention-independence in Experiment 1 but not in Experiment 2 –, and we found perfect masking of the face primes – that is, proof of the subliminality of the prime faces. Based on our findings, we speculate that subliminal facial expressions of disgust could afford easy avoidance of these faces. This could be a unique effect of disgusted faces as compared to other emotional facial displays, at least under the conditions studied here.